2023
DOI: 10.1021/acs.oprd.3c00105
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Chromane-Forming Heck Reaction: Bisphosphine Mono-Oxide Mediated Regioselectivity Perturbed by Solvent-Based Peroxide Formation

Abstract: The development of an exocyclic-selective, chromane-forming Heck reaction is reported. Detailed mechanistic studies revealed the crucial role of a bisphosphine mono-oxide-based Pd complex to promote high exo:endo alkene selectivity (>99:1) in the Heck reaction. Low levels of NMP peroxide in NMP (reaction solvent) can impact this selectivity by overoxidizing the ligand to bisphosphineoxide and promoting catalyst decomposition. The resultant colloidal Pd facilitates isomerization leading to significant levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…As both peptide resins were TFA-cleaved in parallel and in an identical manner, significantly increased Met oxidation during the cleavage of the resin from NBP SPPS seemed unlikely. On the other hand, considering that NMP is readily oxidized to a hydroperoxide byproduct (NMP-OOH) upon standing and as during the SPPS of our Met peptide a several years old R&D batch of NBP was used, we hypothesized that NBP was oxidized to the corresponding hydroperoxide (NBP-OOH) which then caused Met oxidation during the synthesis. To test this theory, we analyzed the batch of NBP at hand by HPLC, which revealed the presence of a 1.75% impurity (Table S20, peak 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As both peptide resins were TFA-cleaved in parallel and in an identical manner, significantly increased Met oxidation during the cleavage of the resin from NBP SPPS seemed unlikely. On the other hand, considering that NMP is readily oxidized to a hydroperoxide byproduct (NMP-OOH) upon standing and as during the SPPS of our Met peptide a several years old R&D batch of NBP was used, we hypothesized that NBP was oxidized to the corresponding hydroperoxide (NBP-OOH) which then caused Met oxidation during the synthesis. To test this theory, we analyzed the batch of NBP at hand by HPLC, which revealed the presence of a 1.75% impurity (Table S20, peak 8).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we report that NBP, a dipolar aprotic solvent that has recently gained increasing usage rates in organic chemistry in general and in peptide synthesis in particular as a viable greener alternative for the hazardous solvent DMF, is susceptible to form hydroperoxide NBP-OOH under a wide range of conditions. While the formation of hydroperoxide NMP-OOH from the structurally related pyrrolidinone NMP and its impact on Heck coupling has been reported, our LC-HRMS assessment of batches of NMP containing NMP-OOH and NBP containing NBP-OOH revealed that aerial oxidation and subsequent processes for NMP and NBP, respectively, proceed by mechanistically distinct pathways. Specifically, while air-exposed NMP has a proclivity to form NMP-OOH followed by deoxygenation to NMP-OH and then oxidation to NMS, for NBP the NBP-OOH formed upon initial oxidation deoxygenates to NBP-OH but then rather than getting oxidized to NBS appears to dehydrate to DNBP, which in turn appears to rearrange to an NBP isomer of a yet undetermined structure.…”
Section: Discussionmentioning
confidence: 99%